Potential association among posterior fossa bony volume and crowdedness, tonsillar hernia, syringomyelia, and CSF dynamics at the craniocervical junction in Chiari malformation type I - Wang, Shengxi; Zhang, Dongao; Wu, Kun; Fan, Wayne; Fan, Tao (Frontiers in Neurology, 2023)
Objective: The characteristic morphological parameters(bony posterior fossa volume (bony-PFV), posterior fossa crowdness, cerebellar tonsillar hernia, syringomyelia) and CSF dynamics parameters at craniocervical junction (CVJ) in Chiari malformation type I (CMI) were measured. The potential association between these characteristic morphology and CSF dynamics at CVJ were analyzed. Methods: Forty-six case of control subjects and forty-eight CMI patients underwent computed tomography and phase contrast magnetic resonance imaging. Seven morphovolumetric measures and four CSF dynamics at CVJ measures were performed. The CMI cohort was further divided into “syringomyelia” and “non-syringomyelia” subgroups. All the measured parameters were analyzed by Pearson correlation. Results: Compared with the control, the posterior cranial fossa(PCF) area, bony-PFV, and CSF net flow were significantly smaller (P< 0.001) in CMI group; Otherwise, the PCF crowdedness index (PCF CI, P< 0.001) and the peak velocity of CSF (P< 0.05) were significantly larger in the CMI cohort. The mean velocity (MV) was faster in CMI patients with syringomyelia (P< 0.05). In the correlation analysis, the degree of cerebellar tonsillar hernia was correlated with PCF CI (R= 0.319, P< 0.05), the MV (R= -0.303, P< 0.05) and net flow of CSF (R= -0.300, P< 0.05). The Vaquero index was well correlated with the bony-PFV (R= -0.384, P< 0.05), MV (R= 0.326, P< 0.05) and net flow of CSF (R= 0.505, P< 0.05). Conclusion: The bony-PFV in CMI patients was smaller, and the MV was faster in CMI with syringomyelia. Cerebellar subtonsillar hernia and syringomelia are independent indicators for evaluating CMI. Subcerebellar tonsillar hernia was associated with PCF crowdedness, MV and net flow of CSF at CVJ, while syringomyelia was associated with bony-PFV, MV and net flow of CSF at CVJ. Thus, the bony-PFV, PCF crowdedness, and the degree of CSF patency should also be one of the indicators of CMI evaluation.